Genetic analysis of dystonia-related genes in Parkinson's disease - Wang, Yige; Zhao, Yuwen; Pan, Hongxu; Zeng, Qian; Zhou, Xiaoxia; Xiang, Yaqin; Zhou, Zhou; Xu, Qian; Sun, Qiying; Tan, Jieqiong; Yan, Xinxiang; Li, Jinchen; et al. (Frontiers in Aging Neuroscience, 2023)
Objective Parkinson's disease (PD) and dystonia are two closely related movement disorders with overlaps in clinical phenotype. Variants in several dystonia-related genes were demonstrated to be associated with PD; however, genetic evidence for the involvement of dystonia-related genes in PD has not been fully studied. Here, we comprehensively investigated the association between rare variants in dystonia-related genes and PD in a large Chinese cohort. Methods We comprehensively analyzed the rare variants of 47 known dystonia-related genes by mining the whole-exome sequencing (WES) and whole-genome sequencing (WGS) data from 3,959 PD patients and 2,931 healthy controls. We initially identified potentially pathogenic variants of dystonia-related genes in patients with PD based on different inheritance models. Sequence kernel association tests were conducted in the next step to detect the association between the burden of rare variants and the risk for PD. Results We found that five patients with PD carried potentially pathogenic biallelic variants in recessive dystonia-related genes including COL6A3 and TH. Additionally, we identified 180 deleterious variants in dominant dystonia-related genes based on computational pathogenicity predictions and four of which were considered as potentially pathogenic variants (p.W591X and p.G820S in ANO3, p.R678H in ADCY5, and p.R458Q in SLC2A1). A gene-based burden analysis revealed the increased burden of variant subgroups of TH, SQSTM1, THAP1, and ADCY5 in sporadic early-onset PD, whereas COL6A3 was associated with sporadic late-onset PD. However, none of them reached statistical significance after the Bonferroni correction. Conclusion Our findings indicated that rare variants in several dystonia-related genes are suggestively associated with PD, and taken together, the role of COL6A3 and TH genes in PD is highlighted.